Serat Kalatidha: Reconstructing Accounting Practices - Tjahjono, Mazda Eko Sri (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to explore the values that exist in modern accounting. The Paradigma Nusantara method is employed in this research. The use of values inherent in modern accounting practices persists, as the value has been attached to these practices. This research is expected to raise individual awareness of the conduct of accounting practices. The Nusantara culture is selected as the approach, as it is characterised by high noble values and is already grounded. The novelty of this research lies in the formulation of new values in accounting practices.